THE EFFECT OF MARKET ORIENTATION ON MARKETING PERFORMANCE THROUGH COMPETITIVE ADVANTAGE AS A MEDIATING VARIABLE (IN SIDOARJO REGENCY MSMES) - Imtiyaz Nazifah Azzahra; Cliff Kohardinata (Antis Publisher, 2025)
Objective: This study examines the effect of market orientation on marketing performance, with competitive advantage as a mediating variable, in the context of MSMEs in Sidoarjo Regency. Given the increasingly competitive business environment, MSMEs must leverage their resources and capabilities to achieve a sustainable competitive advantage and enhance marketing performance. Method: A quantitative research approach was employed, utilizing a survey questionnaire distributed to MSMEs in Sidoarjo Regency. The study applied a purposive sampling technique to select relevant respondents. Data analysis was conducted using Partial Least Squares (PLS) to assess both the measurement and structural models. Results: The findings indicate that market orientation has a significant and positive impact on marketing performance. Additionally, competitive advantage serves as a mediating factor, reinforcing the relationship between market orientation and marketing performance. The results highlight that MSMEs adopting market-oriented strategies can enhance their competitive advantage, ultimately leading to improved marketing performance. Novelty: This study contributes to the existing literature by providing empirical evidence on the mediating role of competitive advantage in the relationship between market orientation and marketing performance within the MSME sector in Sidoarjo Regency. The findings offer practical insights for MSME practitioners to strengthen their competitive strategies through market orientation.